Elbow tendinopathy and occupational biomechanical overload: A systematic review with best‐evidence synthesis. Issue 1 (3rd February 2021) - Curti, Stefania; Mattioli, Stefano; Bonfiglioli, Roberta; Farioli, Andrea; Violante, Francesco S.
Abstract: Objectives: To evaluate the evidence of an association between occupational and non‐occupational exposure to biomechanical risk factors and lateral elbow tendinopathy, medial elbow tendinopathy, and olecranon bursitis. Methods: We carried out a systematic review of the literature. We searched MEDLINE (up to November 2019) and checked the reference lists of relevant articles/reviews. We aimed to include studies where (a) the diagnosis was based on physical examination (symptoms plus clinical signs) and imaging data (if any); and (b) the exposure was evaluated with video analysis and/or direct measurements. A quality assessment of the included studies was performed along with an evaluation of the level of evidence of a causal relationship. Results: We included four studies in the qualitative synthesis: two prospective cohorts and two cross‐sectional studies. All the included studies investigated "lateral/medial epicondylitis", albeit the diagnosis was not supported by imaging techniques. Two cohort studies suggested that a combination of biomechanical risk factors for wrist/forearm is associated with increased risk of "lateral epicondylitis". This association was not observed in the two included cross‐sectional studies. The cohort studies suggested that a Strain Index score higher than 5 or 6.1 could double the risk of "lateral epicondylitis". No association with increased risk of "medial epicondylitis" was observed. Conclusions: There is limited evidence of a causal relationship between occupational exposure to biomechanical risk factors and lateral elbow tendinopathy. For medial elbow tendinopathy, the evidence is insufficient to support this causal relationship. No studies on olecranon bursitis and biomechanical overload were identified.